Improved detection of Burkholderia pseudomallei from non‐blood clinical specimens using enrichment culture and PCR: narrowing diagnostic gap in resource‐constrained settings. Issue 7 (8th June 2017) - Tellapragada, Chaitanya; Shaw, Tushar; D'Souza, Annet; Eshwara, Vandana Kalwaje; Mukhopadhyay, Chiranjay
Abstract: Objectives: To evaluate the diagnostic utility of enrichment culture and PCR for improved case detection rates of non‐bacteraemic form of melioidosis in limited resource settings. Methods: Clinical specimens ( n = 525) obtained from patients presenting at a tertiary care hospital of South India with clinical symptoms suggestive of community‐acquired pneumonia, lower respiratory tract infections, superficial or internal abscesses, chronic skin ulcers and bone or joint infections were tested for the presence of Burkholderia pseudomallei using conventional culture (CC), enrichment culture (EC) and PCR. Sensitivity, specificity, positive and negative predictive values of CC and PCR were initially deduced using EC as the gold standard method. Further, diagnostic accuracies of all the three methods were analysed using Bayesian latent class modelling (BLCM). Results: Detection rates of B. pseudomallei using CC, EC and PCR were 3.8%, 5.3% and 6%, respectively. Diagnostic sensitivities and specificities of CC and PCR were 71.4, 98.4% and 100 and 99.4%, respectively in comparison with EC as the gold standard test. With Bayesian latent class modelling, EC and PCR demonstrated sensitivities of 98.7 and 99.3%, respectively, while CC showed a sensitivity of 70.3% for detection of B. pseudomallei . An increase of 1.6% (95% CI: 1.08–4.32%) in the case detection rate of melioidosis was observed in the study population when EC and/or PCR were used in adjunct to the conventional culture technique. Conclusions: Our study findings underscore the diagnostic superiority of enrichment culture and/or PCR over conventional microbiological culture for improved case detection of melioidosis from non‐blood clinical specimens.